Anatomical study of hypospadias penis using magnetic resonance imaging in children. Issue 1 (February 2022) - Chaudhary, Gyanendra; Yhoshu, Enono; Chauhan, Udit; Ahmed, Intezar; Gupta, Manish Kumar; Piplani, Rajat; Balija, Satya Sree
Summary: Introduction: To assess the various anatomical patterns of the hypospadias penis, anatomical and histological study of the penile tissues, planes, and vascular patterns, and imagings such as ultrasound of penis, elastography, and Magnetic resonance imaging (MRI) of penis have been described in the literature. All these have been done to attempt the identification of anatomical variations that may influence surgical outcomes. There are very limited MRI studies of hypospadias penis to look for the pristine anatomy. Objective: The objective was to identify anatomical variations in hypospadias penis such as the penile tissues and planes and the vascularity using MRI. Material and methods: The total number of patients enrolled was 24 from January 2019 to July 2020. This included all the cases of hypospadias at any location aged ≥5 years. MRI penis was done using 3T (3 Tesla) MRI scanner (GE Healthcare signa 3T Scanner machine) with 3 mm body coil slice thickness and the surface coil of 3 inches. Non-contrast images were taken using fast spin-echo sequences in sagittal, coronal, and transverse planes. The findings analyzed were: presence and distribution of penile tissue and fascial structures, urethral plate thickness, and penile vasculature. Results: The mean age was 7.62 ± 2.14 years. The types of hypospadias included were Coronal 1/24 (4.2%), Subcoronal 14/24 (58.3%), Distal penile 3/24 (12.5%), Midpenile 5/24 (20.8%) and Penoscrotal 1/24 (4.2%) (Summary Table 1). The mean urethral plate thickness was 1.33 ± 0.38 mm. The penile soft tissues were well visualized along with their fascial planes. The majority of patients (91.7%, 22/24) had Superficial Dartos vessels with both branches. Bulbourethral vessel was present in 18 (75.0%) cases but could not be visualized in the rest. Ventral and Lateral Dartos vessels were seen in 20 (83.3%) cases. Perforators distal to meatus were visualized in 21 (87.5%) cases and not visualized in 3 (1 each in Penoscrotal, Midpenile, and Coronal hypospadias). Collaterals at corona sulcus were visualized in 23 (95.8%) cases, at paraurethral spongiosum in 15 (62.5%) cases, and at dorsum in 22 (91.7%) cases. Conclusion: 3T MRI gives precise images in hypospadias with relation to the tissue and fascial planes of the penis. The vascular pattern visualization in these patients may be confirmed by the availability of a dedicated penile coil which will help to improve the resolution of the penile structures. Analyzing the penile vascular pattern and correlating it with surgical outcomes may aid the surgeon's knowledge of hypospadias, develop new surgical techniques and hence reduce complications. Summary Table 1 Details of the patients in the study-age, type of hypospadias and urethral thickness. Summary Table 1 Basic Details Mean ± SD || Median (IQR) || Min-Max || Frequency (%) Age (Years) 7.62 ± 2.14 || 7.00 (6.00–8.25) || 5.00–13.00 Type of hypospadias Subcoronal 14 (58.3%) Midpenile 5 (20.8%) Distal Penile 3 (12.5%) Coronal 1 (4.2%) Penoscrotal 1 (4.2%) Urethral Plate Thickness (mm) 1.33 ± 0.38 || 1.25 (1.00–1.50) || 0.70–2.00